Design of Ammonia Gas Detection and Control Devices in Chicken Farms Based on Arduino Uno - Arnawan Hasibuan; Muhammad Daud; Rahmat Andria; I Made Ari Nrartha; M Sayuti; Fajar Syahbakti Lukman (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Broiler chicken is a superior breed that has high productivity. Ammonia odor that pollutes the area around the cage is a problem in broiler management. Due to the activity of microorganisms in feces, unabsorbed protein amino acids, and other non-protein nitrogen (NPN) compounds break down into ammonia gas. In addition to damaging the environment, NH3 gas can interfere with animal performance, making them susceptible to disease. This research aims to solve the problem that comes from ammonia by measuring and designing an automatic ammonia gas controller based on Arduino using an MQ-135 sensor. If ammonia levels in the cage are greater than 5 ppm, ammonia levels are controlled by spraying liquid smoke to limit ammonia gas emissions. The results of this study show that the tool is able to reduce ammonia gas levels to 8 ppm. Ayam broiler adalah jenis ras unggulan yang memiliki daya produktivitas tinggi. Bau amoniak yang mencemari area sekitar kandang menjadi masalah dalam pengelolaan ayam broiler. Karena aktivitas mikroorganisme dalam feses, protein yang tidak diserap asam amino, dan senyawa nitrogen non-protein (NPN) lainnya terurai menjadi gas amoniak. Selain merusak lingkungan, gas NH3 dapat mengganggu performa hewan, sehingga rentan terkena penyakit. Penelitian ini bertujuan untuk mengatasi masalah yang berasal dari amonia dengan metode pengukuran dan perancangan alat pengontrol gas amoniak otomatis berbasis arduino menggunakan sensor MQ-135. Jika kadar amoniak di dalam kandang lebih besar dari 5 ppm, kadar amoniak dikendalikan dengan penyemprotan asap cair untuk membatasi emisi gas amoniak. Hasil dari penelitian ini alat tersebut mampu menurunkan kadar gas ammonia hingga 8 ppm.